Technology Integration in Education: Bridging the Digital Skills Gap - Sulaiman, Aryati Juliana; Che Pak, Nur Azliani Haniza (2024)
The integration of technology in accounting education is crucial for preparing students to meet the demands of the modern workforce. This paper explores the significance of incorporating technological tools and platforms in accounting curricula, emphasizing the need for faculty readiness and student preparedness. Faculty readiness involves not only the acquisition of technical skills but also the ability to effectively integrate these tools into teaching methodologies. Student preparedness, on the other hand, focuses on equipping learners with the necessary competencies to leverage technology in their future careers. Despite the clear benefits, challenges such as resistance to change, limited resources, and the need for continuous professional development pose significant barriers to successful technology integration. Addressing these challenges requires a collaborative effort from educational institutions, faculty, and students to create a conducive learning environment that embraces technological advancements. Research on how this integration can improve students’ learning experience, particularly in accounting education is limited. Therefore, this study aims to gain insight into faculty and students’ perspectives on technology integration as well as its challenges